Prediction of protein–protein interactions between Theileria parva and Bos taurus based on sequence homology - Kamau, E.; Nyanjom, S.G.; Wamalwa, M. (Oxford University Press, 2016)
Theileria parva induces pathogenesis, characteristic of cancer cell transformation and associated with invasion, proliferation and altered gene expression of infected bovine host leucocytes. Interactions among proteins are an important basis for biological functions and underlie processes essential to pathogenesis during infection. Knowledge or prediction of host–pathogen molecular interactions may suggest mechanisms of pathogen interference and can be useful for selecting potential therapeutic targets. Using information on conserved protein interactions in other organisms (interologs), protein interactions and orthologous relationships were predicted between T. parva parasite and Bos taurus (the bovine mammalian host). Among the predicted interactions were Theileria HSP90 and glutaredoxin-like protein and bovine c-JUN, AKT1, Rac1, STAT3 and HIF-1-α proteins, observed to act as hubs connecting the predicted interactions to protein interactions within host. Bovine proteins were enriched in pathways that reflect known phenotype of Theileria infection such as induction or inhibition of apoptosis signalling, metastasis and tissue invasion, IL-10 signalling, NF-κB/IKK activation, PI-3K pathway, TGF-β signalling, modulation of immune and inflammatory responses. Support vector machine classifiers trained with the predicted interactions identified known protein interactions with 86.22% accuracy, 84.72% precision, 89.88% sensitivity and 84.39% specificity measures. Predicted interactions provide insight into Theileria- and bovine-encoded interactomes that contribute to infection, providing a candidate set for subsequent experimental studies with the possible use for defining functional annotation to uncharacterized parasite proteins.